The Effect of Zeolitic Fertilizer on Nitrogen Retention in Soil and Its Availability to Plants - Ayaz Ahmad; Shahzada Sohail Ijaz; Fengliang Zhao; Hafeez Ullah Rafa; Ghulam Farid (Nitrogen)
Global crop yield is stagnant due to quick release of N from fertilizers and its lower availability at critical growth stages of crops. Urea impregnation of aluminosilicate minerals, especially zeolites, holds NH4+ and delays its release for later crop stages. limited information is available in the literature about the effect of zeolite-based urea fertilizer on soil nitrogen dynamics. Zeolitic urea formulation was prepared and tested in a field experiment under a wheat–rice cropping system. Sources of N were urea and zeolitic urea formulation. N was reduced up to 50% in the treatments from zeolitic urea. Soil parameters (NH4-N, NO3-N, available N and total N) and plant parameters were recorded by following the standard procedures. Zeolitic urea retained the highest contents of NH4-N and NO3-N at critical growth stages (booting and maturity) of wheat crop. Zeolitic urea retained the highest NO3 in 0–30 cm soil depth, while these were highest at 60–90 cm depth with urea. Grain yield of wheat crops with N100%U were similar to that of with N75%ZU, where 25% less N was applied and nitrogen use efficiency was improved to 25.82% by zeolitic urea. Zeolite-based N fertilizer retains N in soil for an extended period of time and maintains crop yield even with less applied N as compared with urea.